Inclusive Vision Versus Special Education Reality - James M. Kauffman; Garry Hornby (MDPI AG, 2020)
The reasons are examined for the disparity between the inclusive vision espoused by Article 24 of the United Nations Convention on the Rights of Persons with Disabilities and the reality of the limited extent of inclusion in education systems worldwide. First, the leadership of key senior academics in the field of special education is considered to have been misguided in promoting a vision of full inclusion despite the lack of research evidence for the benefits of inclusive education over traditional special education provision. Second, attitudes toward and the treatment of people with disabilities have a long and complex history, and in this, many proponents of inclusion have been critical of 20th century special education. In particular, they claim that the sorting, labelling and categorizing required by special education have negative implications. Third, educators have been encouraged to imagine a system of education that is limitless, in the sense that all children with disabilities can be included in general education. This is because it is envisaged that general education classrooms will become so flexible that there will be no limits to the accommodation of students with disabilities, regardless of the nature or severity of their special educational needs. Fourth is the issue that deciding a student's placement for education requires a judgment call and that, since human judgment is fallible, errors of judgment will always be made. Fifth, commitments to inclusion require that educators consider the practical, reality-based implications, whereas this has not been the case for many supporters of full inclusion. In conclusion, inclusion in the sense of students being physically present in general education classrooms is not considered as important as inclusion in the reality of being engaged in a program of instruction that is meaningful and challenging. Therefore, we consider that, rather than becoming extinct, special education needs to continue to be developed, disseminated and rigorously implemented in schools. Key special education strategies and approaches must co-exist with those from inclusive education, in order to provide effective education for all young people with special educational needs and disabilities.